Outcome of adjuvant radiotherapy after total hysterectomy in patients with uterine leiomyosarcoma or carcinosarcoma: a SEER-based study - Li, Yuan; Ren, Haitao; Wang, Junmei (BMC cancer, 2019)
The clinical impact of adjuvant radiotherapy on uterine sarcoma is unclear, and may depend on the histological type. Hence, the aim of this study was to evaluate clinical outcomes of adjuvant radiotherapy after total hysterectomy in patients with leiomyosarcoma or carcinosarcoma. Data were obtained from the Surveillance, Epidemiology, and End Results (SEER) program. Cox proportional hazards regression analyses were performed to identify risk factors for overall mortality and cancer-specific mortality. In addition, a 1:1 propensity score matching approach was performed, in which age group, disease stage, tumor grade, tumor size, and lymphadenectomy status were matched. A total of 566 leiomyosarcoma and 1069 carcinosarcoma patients with stage I-III disease were included. Both regular Cox regression analysis and propensity score matching analysis revealed that utilization of adjuvant radiotherapy did not affect overall and cancer-specific mortality in patients with leiomyosarcoma. In contrast, for patients with carcinosarcoma, total mortality risk was significantly decreased with EBRT, brachytherapy, and combination radiotherapy compared with no radiotherapy. Cancer-specific mortality risk was significantly decreased with brachytherapy and combination radiotherapy as compared with no radiotherapy. Propensity score matching analyses revealed similar results in overall mortality, but not cancer-specific mortality, in patients with carcinosarcoma. Furthermore, the frequency of patients who did not receive any form of adjuvant radiotherapy was four times higher than those underwent adjuvant radiotherapy. Adjuvant radiotherapy may provide a survival benefit for uterine carcinosarcoma, but not leiomyosarcoma. In addition, adjuvant radiotherapy is underutilized, and increased utilization of adjuvant radiotherapy may improve the survival rate of patients with carcinosarcoma.